Let's choose the number \( 1.95 \times 10^6 \) and divide it by \( 0.3 \).
We start with the expression:
\[ \frac{1.95 \times 10^6}{0.3} \]
First, we can rewrite \( 0.3 \) in scientific notation:
\[ 0.3 = 3.0 \times 10^{-1} \]
Now we substitute:
\[ \frac{1.95 \times 10^6}{3.0 \times 10^{-1}} \]
Next, we can divide the coefficients (the numbers in front) and then subtract the exponents (according to the rules of exponents):
\[ = \frac{1.95}{3.0} \times 10^{6 - (-1)} \]
Calculating \( \frac{1.95}{3.0} \):
\[ 1.95 \div 3.0 = 0.65 \]
Now we simplify the exponent:
\[ = 0.65 \times 10^{6 + 1} = 0.65 \times 10^7 \]
Next, we want to express \( 0.65 \) in scientific notation:
\[ 0.65 = 6.5 \times 10^{-1} \]
So we can substitute that back into our expression:
\[ 0.65 \times 10^7 = 6.5 \times 10^{-1} \times 10^7 \]
Finally, we combine the powers of 10:
\[ = 6.5 \times 10^{7 - 1} = 6.5 \times 10^6 \]
Thus, the final result of dividing \( 1.95 \times 10^6 \) by \( 0.3 \) is:
\[ \boxed{6.5 \times 10^6} \]